Extra Cellular Matrix Remodeling: An Adjunctive Target for Spinal Cord Injury and Intervertebral Disc Degeneration - Ashish Kumar; Neeraj Kumar; Zarna Pathak; Hemant Kumar (Neurospine, 2022)
The extracellular matrix (ECM) is a protein-and-carbohydrate meshwork that supports a variety of biological structures and processes, from tissue development and elasticity to the preservation of organ structures. ECM composition is different in each organ. It is a remarkably dynamic 3-dimensional structure that's constantly changing to maintain tissue homeostasis. This review aims to describe the involvement of ECM components in the remodeling process of spinal cord injury (SCI) and intervertebral disc degeneration (IVDD). Here, we have also described the current ECM-based therapeutic targets, which can be explored for ECM remodeling SCI is a neurological condition with intense influences resulting from a trauma inflicted on the spinal cord. SCI leads to damage to the intact ECM that leads to regeneration failure. IVDD mainly occurs due to aging and trauma. Various ECM components enable fragmentation of the disc and are thereby involved in disc degeneration. ECM manipulation can be used as an adjunct treatment in SCI and IVDD. Current treatment approaches for SCI and IVDD are conservative and unsatisfactory. Targeting ECM remodeling as an adjunct therapy may result in better disease outcomes.